Revitalisasi Nilai-Nilai Piil Pesenggiri sebagai Kearifan Lokal dalam Ketahanan Budaya Lampung - Novri Rahman; Muarafa Nur Afif (Advances In Education Journal, 2025)
Piil Pesenggiri is a philosophy of life of the Lampung people that represents a system of values, social ethics, and cultural identity passed down across generations. However, the process of modernization and the flow of globalization have driven a shift in values ​​that has weakened the younger generation's understanding of the substantive meaning of Piil Pesenggiri. This study aims to examine the role of Piil Pesenggiri values ​​in strengthening the cultural resilience of the Lampung people and identifying relevant revitalization strategies in the context of modern culture. The research method uses a descriptive qualitative approach through a literature review of classical manuscripts and ethnographic studies, including the works of Hadikusuma (1977/1978) and Sayuti (1985). The results show that the four main values ​​of Piil Pesenggiri nemui nyimah, nengah nyappur, sakai sambayan, and juluk adok function as pillars of social morality that maintain harmony, self-esteem, and community solidarity. Revitalization of these values ​​can be done through culture-based education, strengthening traditional activities, and integration in the local content curriculum so that Lampung's local wisdom remains alive, adaptive, and relevant in facing the dynamics of social change..